The Use of The Instagram Application as an Excretory System Material Learning Medium to Enhance Students Creativity and Learning Outcomes - Shindy Santika Maharani; Aditya Marianti (Universitas Negeri Semarang, 2024)
The era of the industrial revolution 4.0 is an era that views information technology as a basic need in human life, including in the field of education. Biology teachers are expected to have skills in utilizing information technology as a learning medium. One of the social media that can be used as a learning medium is Instagram. Instagram has interesting features that can stimulate student creativity. The purpose of this study was to analyze the use of Instagram as a learning medium for increasing creativity and student learning outcomes. This research is a quasi-experimental by looking at the comparison of creativity and learning outcomes of the experimental class using the Instagram application and the control class using PowerPoint media. The learning model used is Discovery Learning with the help of the Instagram application as a learning medium. The results of this study show the percentage increase in student creativity in the good category. Student learning outcomes cannot be said to be complete because they have not reached 75% completeness, but based on the n-gain test they are in the moderate category. From the hypothesis test, it is obtained that t-count is greater than t- . The results of this analysis show that the use of Instagram media as a learning medium influences creativity and student learning outcomes. The results of the student response questionnaire to the use of Instagram as a learning medium showed results of 79.19% in the good category. The conclusion from this study is that the use of Instagram media as a learning medium can increase the creativity and learning outcomes of students in the experimental class.